CUSTOMER SATISFACTION ANALYSIS ON LEMANG TAPAI TRADITIONAL FOOD AT BENGKULU - Rexy Pratama Jayadi; Zulman Effendi; Marniza Marniza (Jurnal Agroindustri, 2019)
The purpose of this study is to get attribute desired customer, determine satisfaction customer againt of “lemang tapai”, and to get quality priority the attributes lemang tapai. The sampling techniqueof this study is accidental sampling to dicided 100 respondents. The method of analysisis test validity and reliability, determine custumer satisfaction indexs (CSI) and determine importance performance analisys (IPA). The result of this study show that attributes desirable customer lemang tapai is a sense of lemang, texture of lemang, colors of lemang, aroma of lemang, bamboo whitout a disability and crack, flawed prevent burning, sense of tapai, texture of tapai, colors of tapai and aroma of tapai. The resut of CSI show the level of satisfaction customer of lemang tapai 0,82. The attributes of lemang tapai that recommended for quality repair by producers is aroma of tapai.